China and the Countries of the Global South: Uruguay and China Economic Cooperation at the Beginning of the 21st Century - Olga V. Volosyuk; Carlos Quiroga Cremella (Vestnik RUDN. International Relations)
The article examines the development of relations between China and Latin America, focusing on economic cooperation with Uruguay. The study analyzes the formation of a new economic and political landscape in the Global South, highlighting the specific aspects of China’s policy in this region. The authors identify two key phases in the bilateral relationship between China and Uruguay, spanning nearly twenty-five years, with the 2016 agreement marking a significant milestone in establishing a strategic partnership between the two countries. Using the Global South as a theoretical and methodological marker for scientific inquiry requires a clear methodological framework built around the conceptual parameters of the Global South itself. Uruguay’s approach to the Global South concept is methodologically crucial, given its balanced and moderate foreign policy stance. The article demonstrates how China, seeking to strengthen its position in Latin America, is developing a comprehensive policy to increase trade turnover and investments in the region. Specifically, the dynamics of export and import between China and Uruguay are examined, as well as Uruguay’s role as a strategic partner for China. The authors analyze Uruguay’s legal and institutional environment that facilitates foreign investment and note that despite significant successes in trade, the level of Chinese investments in Uruguay remains relatively low. The article goes on to explore potential reasons for this phenomenon and the prospects for further development of investment cooperation. Special attention is given to the role of the Belt and Road Initiative (BRI), which Uruguay joined in 2018, thus becoming the first Southern Common Market (MERCOSUR) member to support this Chinese initiative. The article underscores the importance of further deepening the strategic partnership between China and Uruguay, which can serve as a successful example of interaction within the Global South and contribute to the strengthening of the positions of Global South countries on the international stage.